Hubungan Antara Stres Akademik Dengan Prokrastinasi Akademik Pada Mahasiswa - Astari, Amarul Zulfiya; Nastiti, Dwi (ResearchJet Journal of Analysis and Inventions, 2024)
This study aimed to determine the relationship between academic stress and academic procrastination among students at Muhammadiyah Sidoarjo University. The type of research uses quantitative correlational. The total population of 10802 students with a sample of 336 students taken by simple random sampling technique. Data collection techniques using a Likert scale. The validity of academic stress uses 14 valid items. The validity of academic procrastination uses 20 valid items. Academic stress reliability results of 0.780 from 14 items. The results of academic procrastination reliability were 0.853 out of 20 items. The data analysis technique uses Spearman's product moment assisted by SPSS 25.0. The results of data analysis obtained rxy = 0.365 with sig 0.000 <0.05. Then the hypothesis is accepted which means there is a positive relationship between academic stress and academic procrastination.